2018
DOI: 10.1111/joa.12900
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional analysis of shape variations and symmetry of the fibula, tibia, calcaneus and talus

Abstract: The bones forming the talocrural joint (TCJ) and subtalar joint (STJ) are often assumed to be bilaterally symmetric. Therefore, the contralateral limb (i.e. the fibula, tibia, calcaneus and talus) is used as a template or an intra‐subject control in clinical and research practice. However, the validity of the symmetry assumption is controversial, because insufficient information is available on the shape variations and bilateral (a)symmetry of the fibula, tibia, calcaneus and talus. Using three‐dimensional spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
65
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 43 publications
15
65
2
Order By: Relevance
“…The high degree of symmetry is in line with earlier studies that have demonstrated a high degree of symmetry in the lower extremity (Latimer and Lowrance, 1965). Specifically for the hindfoot, a strong degree of symmetry was demonstrated for the whole talus (Islam et al, 2014), the calcaneus (Stephan et al, 2014) and tibia, fibula, talus, and calcaneus (Tümer et al, 2018). A clear cause for the asymmetry in type 12100% 80The diagonal with bold numbers represent the corresponding classifications between the two observers.…”
Section: Bilateral Symmetrysupporting
confidence: 87%
See 1 more Smart Citation
“…The high degree of symmetry is in line with earlier studies that have demonstrated a high degree of symmetry in the lower extremity (Latimer and Lowrance, 1965). Specifically for the hindfoot, a strong degree of symmetry was demonstrated for the whole talus (Islam et al, 2014), the calcaneus (Stephan et al, 2014) and tibia, fibula, talus, and calcaneus (Tümer et al, 2018). A clear cause for the asymmetry in type 12100% 80The diagonal with bold numbers represent the corresponding classifications between the two observers.…”
Section: Bilateral Symmetrysupporting
confidence: 87%
“…Despite the known variation only two studies analyzed the degree of bilateral symmetry of the facet joints: one describing the pattern of calcaneal facets (Ragab et al, 2003), and another one describing the surface area and three-dimensional (3D) orientation of the calcaneal facets (Stephan et al, 2014). In general, literature describing the bilateral symmetry of the hindfoot is scarce (Shultz and Nguyen, 2007;Islam et al, 2014;Tümer et al, 2018). This is remarkable since many surgeons use the contralateral noninjured side as reference for anatomical reduction in case of a fractured bone (Pierre et al, 2010;Dobbe et al, 2011;Young et al, 2013;Ten Berg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2019)'s study supports the current study's findings around the deviation contour of PC2 in the area of the talar dome ( Figure 5). In addition, Tümer et al (2019) revealed that the principal FIGURE 5 | The percentage of points with the deviation >1 mm in the first five PCA eigenvectors scaled by +3σ and its mean shape for male and female.…”
Section: Discussionmentioning
confidence: 99%
“…In the alignment procedure (Fig. , step 3), each bone sample was first translated to the origin of a common coordinate system and was then scaled to the unit centroid size . Then, an evolving mean shape was fit to each bone sample described by a point cloud (i.e., a set of points sampled across all the surfaces of the bone sample).…”
Section: Methodsmentioning
confidence: 99%
“…Then, an evolving mean shape was fit to each bone sample described by a point cloud (i.e., a set of points sampled across all the surfaces of the bone sample). The registration parameters that needed to be input by the user (i.e., the scaling parameter for the mixture of Gaussians, σ , the number of points in the mean cloud, n m , and the trade‐off parameter, λ ) were retrieved from our previously published studies for the tali ( σ = 3 mm, n m = 2,000, λ = 10 −6 ) and calcanei ( σ = 3 mm, n m = 2,000, λ = 5 × 10 −4 ) …”
Section: Methodsmentioning
confidence: 99%